IMPLICATIONS OF TRANSGENDER ON MARITAL STATUS FROM THE PERSPECTIVE OF MEDAN CITY SCHOLARS - Rambe, Rachmat Husein; Syam, Syafruddin; Firmansyah, Heri (International Journal of Cultural and Social Science, 2026)
The phenomenon of gender reassignment (transgender) presents complex legal issues, particularly concerning marital status from an Islamic legal perspective. This research examines the Islamic view on gender reassignment, the validity of marriage post-reassignment, and the implications on marital status according to scholars in Medan City. Using a qualitative method with a normative-sociological approach, data was gathered through a literature review and interviews with scholars from the Indonesian Ulema Council (MUI), Muhammadiyah, and Al-Washliyah. The findings show that Islamic law views intentional sex reassignment, without medical reasons, as contrary to human nature and impermissible. While the marriage contract remains valid, gender reassignment disrupts the marital essence, rendering the marriage unsustainable. Medan scholars believe that gender reassignment does not invalidate the marriage but provides a strong basis for ending it through Islamic legal mechanisms, with fasakh being the most just solution. This research contributes to Islamic family law studies, emphasizing the Sharia-oriented approach in addressing transgender issues.